Enhancing Science Literacy and Collaboration Skills Through the RADEC Learning Model in Junior High Schools - Sofira, Anis; Rahayu, Rina; Trisnowati, Eli (Jurnal Pendidikan MIPA, 2025)
Collaboration and science literacy skills are key indicators in the current learning era. Collaboration trains students to actively engage and make decisions together, while science literacy equips them to think critically and face the challenges of the Industrial Revolution. However, in reality, both skills remain below average among students. This gap highlights the need for an effective learning model to address the problem. Several studies have shown that the Read, Answer, Discuss, Explain, and Create (RADEC) learning model can improve these abilities through a structured and student-centered approach. The objectives of this study are to analyze the effectiveness of the RADEC learning model in improving students' science collaboration and literacy. This research used a quasi-experimental nonequivalent control group design. The sample consisted of class VIII C (experimental) and VIII D (control), selected through purposive sampling. Data were obtained from a collaboration skills questionnaire and students’ pretest and posttest scores to assess improvements in science literacy skills. The results showed that (1) the RADEC model is effective in improving students' science collaboration skills from the t-test with sig (2-tailed)-value is less than 0.05 which means that the structured RADEC model can facilitate the development of affective and cognitive aspects to create a high collaborative learning environment and (2) the RADEC model is effective in improving students' science literacy skills from the t-test with sig (2-tailed)-value is less than 0.05 which means that the RADEC model through its stages is able to build better conceptual understanding to develop students' science literacy significantly. This study concludes that the RADEC learning model is effective in improving the science collaboration skills and science literacy of junior high school students.    Keywords: RADEC, science collaboration skill, science literacy.